2017
DOI: 10.1186/s12955-017-0742-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PDQ-8 and its relationship with PDQ-39 in China: a three-year longitudinal study

Abstract: BackgroundParkinson’s disease is characterized by motor and non-motor symptoms with wide ranging impacts on the health-related quality of life. The 39-item Parkinson’s disease Questionnaire (PDQ-39) is the most widely used PD-specific health-related quality-of-life questionnaire. The short-form 8-item Parkinson’s disease Questionnaire (PDQ-8) was found to produce results similar to that of the PDQ-39 cross-culturally. However, there is no evaluation of the PDQ-8 in the mainland of China.MethodsIn this longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Nevertheless, a strength of our study is that the questionnaires PDQ-8 and EQ-5D-5L have been validated both in PD patients and in Greek language. Furthermore, the current study confirmed existing published data on PDQ-8 [ 12 , 16 , 18 , 20 , 21 , 72 , 83 85 ], thus adding to the credibility of the results for PDQoL7. Additionally, the conduct of the study by trained neurologists specialized in movement disorders encompasses an ascertainment of a high level of accuracy in the recognition and evaluation of the different clinical symptoms and signs of the disease.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, a strength of our study is that the questionnaires PDQ-8 and EQ-5D-5L have been validated both in PD patients and in Greek language. Furthermore, the current study confirmed existing published data on PDQ-8 [ 12 , 16 , 18 , 20 , 21 , 72 , 83 85 ], thus adding to the credibility of the results for PDQoL7. Additionally, the conduct of the study by trained neurologists specialized in movement disorders encompasses an ascertainment of a high level of accuracy in the recognition and evaluation of the different clinical symptoms and signs of the disease.…”
Section: Discussionsupporting
confidence: 88%
“…The validity of grouping the items of PDQ-39 and its 8-item short form (PDQ-8) in 8 domains and the initially proposed unidimensionality of PDQ-39 have been questioned [ 70 , 71 ]. The available evidence suggests, though not confirming, that PDQ-39 may be multidimensional with 3 HRQoL domains, namely physical-functioning, cognition, and socioemotional [ 11 , 14 16 , 70 , 72 ]. PDQoL7 was also found to be multidimensional with 3 domains.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were asked to choose a number from 0 to 10 to represent their understanding of the disease; the higher score indicated that they knew more disease-related knowledge. The QoL of PD patients was evaluated using PD Questionnaire 8 (PDQ-8), which contained eight items: (1) mobility; (2) activities of daily living; (3) emotional well-being; (4) stigma; (5) social support; (6) cognitions; (7) communication; and (8) bodily discomfort (19)(20)(21)(22)(23), ranging from 0 (normal) to 100 (worst disability). The PDQ-8, developed by (24), is a specialized scale for evaluating the quality of life of PD patients (25).…”
Section: Covariatesmentioning
confidence: 99%
“…The sample size in the studies varied from 24 [28] to 537 [29]. The majority of the participants were in their mid to late 60s, and their mean age ranged from 47.9 years [30,31] to 72 years [32]. The most commonly used tools were the…”
Section: Study Characteristicsmentioning
confidence: 99%